A short review on Ni-based catalyst supporter for carbon monoxide (CO) methanation process. Issue 1 (1st April 2022) - Hatta, A.H.; Jalil, A.A.; Hassan, N.S.; Hamid, M.Y.S.; Rahman, A.F.A.; Aziz, M.A.H.
Abstract: Since the discovery of methane synthesis by the interaction between carbon oxide and hydrogen by Sabatier and Senderens in 1902, the methanation reaction has been extensively established and is frequently utilized in chemical manufacturing, comprising the elimination of trace quantities of CO from feed gas containing a rich amount of hydrogen, refining of the reformate gas for fuel cells, and production of new energy sources, which is synthetic natural gas (SNG). It is feasible for SNG to be carried and distributed using the present pipeline infrastructure, which is favourable from a cost-effectiveness standpoint. Since CO methanation is highly exothermic, the development of exceedingly effective catalysts with promising activity in the CO methanation process is essential to address this problem. Because of their economical price and high catalytic performance, nickel-based catalysts have been extensively studied as CO methanation catalysts. Coke deposition and Ni sintering invariably occur on Ni-based catalysts, and these catalysts also have inadequate low-temperature activity and stabilities. So, the advancement of exceedingly effective nickel-based catalysts with outstanding low-temperature catalytic capabilities has emerged as the primary research attention as well as a significant technical encounter in this sector. This brief overview covers recent developments for a supporter for extremely efficient nickel-based catalysts for CO methanation.